The potential of using olive cake in power generation in the Palestinian territories - Tareq Abu Hamed; Lina Ismail; Aiman Alshare (International Journal of Sustainable Energy, 2017)
Palestine faces considerable challenges relating to its energy supply, which is reflected in its dependency on imported electricity and fuels. This makes it vulnerable to changing political and economic situations and emphasises the urgent need to search for alternative and sustainable sources of energy from within Palestine itself. This study explores the potential energy generation from olive cake (OC) in the Palestinian territories. The findings of the study confirmed that there is a high-energy potential to be derived from OC and that powering olive mills by small-scale generators using OC is feasible. It was found that the amount of electricity that can be produced by OC combustion constitutes about 1.3% of all electricity consumption in 2009. Furthermore, numerous environmental benefits can be derived from using OC as biomass, notably the reduction of hazardous emission and the reduction of untreated OC.